Phytoremediation of mixed reactive Azo dyes in contaminated water by Ceratophylum demersum and its toxicity analysis on other life forms - JV, Priyanka; Gayathri Krishnaswamy, Veena (SPC Journal of Environmental Sciences, 2019)
Textile dyes are toxic in nature as they exert various harmful effects on living organisms. These effluents are the main source pollutant to various ecosystems, especially to soil. In this study, mixed azo dye from a local fabric dyeing industry were analysed for their toxicity effects on Trigonella foenum graecum, Lampito mauritii, and bacterial pathogens. The results presented in the study showed that the toxicity of the mixed azo dye prompted Trigonella foenum graecum root and shoot growth inhibition on 1000 ppm of mixed azo dye contaminated soil, and this effect decreased when performed on remediated soils with higher concentrations of the effluents. Phytoremediation of water contaminated with different concentrations of mixed azo dye solutions was performed using Ceratophylum demersum where, the dye removal percentage was minimal and the plant couldn’t sustain more than 500 ppm of dye. Dye toxicity on earth worms showed increased percentage of protein content of the body in response to stress (azo dye). These results revealed that the textile dyes we toxic to eukaryotic cells and that can potentially lead to adverse health conditions. Further their toxicity was also tested against earthworms and pathogenic bacterial strains.